RESEARCH OF STRUCTURAL AND MECHANICAL PROPERTIES OF MEAT AS AN OBJECT OF PROCESSING IN MEAT COMMINUTOR - YAREMCHENKO, OLEKSANDR; PUKACH, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This paper proposes the use of micro mimics, small facial muscle movements that are difficult to detect with the naked eye, for the assessment of psychological states using artificial intelligence. The aim of the research is to develop and improve methods for the analysis of micro mimics to accurately recognize emotions and psychological states of individuals. In this study, we conducted an experimental investigation of the proposed method using video recordings of individuals in various emotional states. Additionally, our approach has several advantages over previous methods in micro mimics analysis. For instance, our method does not rely on manual annotation, which is time-consuming and prone to human error. Instead, our approach uses an automated process that is more efficient and consistent. In comparison with the previous studies, the proposed method has several advantages, including real-time analysis of micro mimics, the capability to handle large-scale datasets, and the ability to analyze complex facial expressions. Moreover, the proposed method overcomes the limitations of traditional machine learning algorithms, which are less effective in capturing the temporal dependencies in video data. Overall, the proposed method has demonstrated promising results in micro mimics analysis and provides a solid foundation for future research in the field of emotional AI. In conclusion, the results of our experiment and their comparison with the results of previous research demonstrate the effectiveness and applicability of our proposed method in analyzing micro mimics for assessing the psychological state using deep learning algorithms. This study contributes to the field of emotional AI and opens up new opportunities for the assessment of psychological states using micro mimics. The results of this study could be useful in a variety of applications, including mental health, human-computer interaction, and social robotics.
Keywords: Micro mimics; emotional AI; psychological state; artificial intelligence; facial expression recognition; machine learning; video analysis; emotion recognition; human-computer interaction; mental health